Hydrophobically associating acrylamide‐based copolymer for chemically enhanced oil recovery. Issue 4 (13th June 2013) - Ye, Zhongbin; Feng, Mingming; Gou, Shaohua; Liu, Man; Huang, Ziyan; Liu, Tongyi
ABSTRACT A hydrophobically associating copolymer was prepared by free‐radical polymerization with acrylamide (AM), acrylic acid (AA), and N‐allyloctadec‐9‐enamide (NAE) as monomers. The structure was characterized by Fourier transform infrared spectroscopy, 1H‐NMR, 13C‐NMR, and scanning electron microscopy. The rheological experiments indicated that the copolymer possessed superior properties compared with partially hydrolyzed polyacryamide. It was found that an AM/AA/NAE/Tween‐80 system could effectively decrease the interfacial tension and reduce the surfactant loss caused by stratum adsorption in polymer–surfactant flooding. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 2901–2911, 2013